ANALISIS MAKNA DIKSI LIRIK LAGU â€œSATUâ€ MILIK DEWA 19 DENGAN MENGGUNAKAN PENDEKATAN SEMIOTIK - Mimin Mimin; Wikanengsih Wikanengsih; Aditya Permana (Parole : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
A song that has lyrics with a deep meaning or meaning is always popular even though it has been lyrical for a long time, in the creation of song lyrics, there are language games such as games in language style and word meanings. Dhani's songs with Dewa 19 are often judged to have controversial lyrics in the lyrics, the word "I" and the "You" do not always describe someone who is expressing feelings with their soulmate. The owner of this song also often describes the relationship between man and the creator. The song 'Satu' is an example. This research is to analyze a meaning in the one song lyrics. The method used is descriptive qualitative method by dividing the lyrics into several verses, with a semiotic approach the song lyrics are divided into markers and signs and then analyzed to determine their meaning. The research was carried out in several steps, (1) determining the song, (2) dividing it into several verses, (3) determining the markers and signs, (4) analyzing the meaning, (5) describing the results. The results of the authorâ€™s analysis on the lyrics of the song Satu Dewa 19 by Ahmad Dhani concluded that the lyrics contain meaning that implies oneâ€™s obedience to God.